Is vitamin D deficiency a risk factor for recurrent aphthous stomatitis? A systematic review and meta-analysis - Al-Maweri, Sadeq Ali; Halboub, Esam; Al-Sufyani, Ghadah; Alqutaibi, Ahmed Yaseen; Shamala, Anas; Alsalhani, Anas (John Wiley & Sons, 2020)
Objectives A few studies have associated vitamin D deficiency with the occurrence of recurrent aphthous stomatitis (RAS). Hence, the aim of the present systematic review and meta-analysis is to explore such a potential association. Methods A comprehensive search of PubMed, Scopus, and Web of Science databases was conducted in June 2019. The inclusion criteria were (a) observational studies that assessed the relationship between vitamin D and RAS, and (b) the outcome measures reported quantitative vitamin D levels. Studies without control groups, case series, case reports, experimental studies, letter to editors, reviews, were excluded. The random effects model was conducted for meta-analyses using RevMan 5.3 software. Results Five studies comprising 208 RAS patients and 241 healthy individuals were included. All studies except one reported significantly lower levels of vitamin D in RAS patients compared with the healthy individuals. The results of the pooled 5 studies revealed statistically significant lower levels of vitamin D in RAS patients (Mean Difference (MD) = ?9.67 ng/ml, 95% CI = ?15.68, ?3.65; p ? .002). Conclusion The present meta-analysis suggests a significant association between low vitamin D levels and RAS. Further well-designed studies with adequate sample sizes are required to elucidate the role of vitamin D in pathogenesis of RAS.